Creating a National Specimen Referral System in Guinea: Lessons From Initial Development and Implementation - Standley, Claire J.; Muhayangabo, Rigo; Bah, Mamadou S.; Barry, Alpha M.; Bile, Ebi; Fischer, Julie E.; Heegaard, Will; Koivogui, Lamine; Lakiss, Said K.; Sorrell, Erin M.; VanSteelandt, Amanda; Dahourou, Anicet G.; et al. (Frontiers in Public Health, 2019)
In the wake of the 2014–2016, West Africa Ebola virus disease (EVD) outbreak, the Government of Guinea recognized an opportunity to strengthen its national laboratory system, incorporating capacity and investments developed during the response. The Ministry of Health (MOH) identified creation of a holistic, safe, secure, and timely national specimen referral system as a priority for improved detection and confirmation of priority diseases, in line with national Integrated Disease Surveillance and Response guidelines. The project consisted of two parts, each led by different implementing partners working collaboratively together and with the Ministry of Health: the development and approval of a national specimen referral policy, and pilot implementation of a specimen referral system, modeled on the policy, in three prefectures. This paper describes the successful execution of the project, highlighting the opportunities and challenges of building sustainable health systems capacity during and after public health emergencies, and provides lessons learned for strengthening national capabilities for surveillance and disease diagnosis.